Properties of the earliest clonogenic hemopoietic precursors to appear in the developing murine yolk sac. - Wong, P M (1986)
We have found that a variety of clonogenic hemopoietic cells can be obtained in a viable state from mouse conceptuses as early as day 7 of gestation when tissues are disaggregated in a crude collagenase solution containing fetal bovine serum. Examination of the time course of colony formation, and the ultimate size and lineages represented in colonies produced in semisolid medium containing methylcellulose, together with analysis of individual erythroid colonies stained with rabbit antisera specific for adult (HbA) and embryonic (HbE) mouse hemoglobins, revealed the presence on days 7 and 8 of gestation (but not later) of erythropoietic progenitors that give rise to mature erythroid colonies containing up to 100 HbE-containing erythroblasts after 4-6 days of growth in culture. These progenitors are highly sensitive to the disaggregation conditions used. Clonogenic progenitors of exclusively HbA-positive erythroblasts can also be detected in the day-7 conceptus. Assays of progenitors from separately disaggregated yolk sacs and embryos from day-8 conceptuses yielded colonies only from yolk sac suspensions, and again these contained either HbE- and HbA-positive erythroblasts or only HbA-positive erythroblasts. These findings demonstrate the very early appearance in the yolk sac of a population of erythroid progenitors with a number of unique properties. Although most of these yield HbE-positive erythroblasts in vitro, some produce erythroblasts containing HbA only. Such a developmental pattern is consistent with the hypothesis that definitive erythropoiesis in the mammalian fetal liver is derived from stem cells that originate in the yolk sac blood islands.